Socialization Of Online Sales Information System For UMKM Products At Teman Studio Creative - Nagib, Ibrahim; Surya, Iwang Moeslem Andika; Cahyanto, Triawan Adi (Journal Of Humanities Community Empowerment, 2023)
This article discusses a community service activity focused on introducing and training in the field of e-commerce, specifically to support Usaha Mikro, Kecil dan Menengah (UMKM) through collaboration with Teman Studio. Conducted in October 2022, the implementation method included needs research, workshops and training, implementation and mentoring, socialization, as well as monitoring and evaluation. Teman Studio, a Personal Freelance based in Jember, East Java, developed the dewastore.com e-commerce website to facilitate online transactions between sellers and buyers. The activity involved training on the basics of e-commerce, website creation and management, as well as digital marketing strategies. The results of this activity showed an increase in understanding and skills of the participants in managing and using the e-commerce system. The system performance evaluation indicated a positive response from the respondents, with the majority giving high ratings to the developed system. The conclusion from this activity is that the socialization and training on e-commerce successfully enhanced the skills and understanding of UMKMs regarding the use of information technology in their businesses